Developing 21st-Century Skills in Elementary School Students Through Artificial Intelligence - Ari Diana Dwi Susanti (Pedagogik Journal of Islamic Elementary School, 2025)
This research aims to analyze the effectiveness of using Artificial Intelligence (AI) in developing 21st-century skills in elementary school students. This research methodology is literature research, which involves collecting articles from Google Scholar in 2024 using keywords AI, learning effectiveness, and 21st-century skills. Thirty-eight articles were determined using a simple random sample technique. The article is then analyzed with the help of the application of Voyant tools and interpreted to obtain an in-depth meaning. The research results show that using AI is effective for elementary school students to develop 21st-century skills, including critical thinking skills, creativity, communication, and collaboration skills. Research findings show that AI has a significant impact on human life. The positive impact of using AI is efficiency, while the adverse effect is the anxiety that arises (AI Anxiety) and dependence on technology. This research implies that AI must be appropriate and careful without relying entirely on technology.